Extraordinary 21st Century Drought in the Po River Basin (Italy) - Abel Andrés Ramírez Molina; Glenn Tootle; Giuseppe Formetta; Thomas Piechota; Jiaqi Gong (Hydrology)
Recent research identified 2022 as being the year of lowest seasonal April–May–June–July (AMJJ) observed streamflow for the Po River Basin (PRB) in the past two centuries. Expanding upon this research, we applied filters (2-year to 30-year filters) to the AMJJ observed streamflow and identified the late 20th and 21st century as displaying extreme drought. In this study, we introduce PALEO-RECON, an automated reconstruction tool developed to leverage tree ring-based proxies and streamline regression processes. Using PALEO-RECON, we reconstructed the AMJJ streamflow, applying traditional regression techniques and using a nested approach in which 30-, 40-, and 50-year windows within the ~200-year observed streamflow record (1807 to 2022) were evaluated to capture uncertainty. Focusing on the 21st century (2000 to 2022), while several droughts in the ~2000-year paleo record may have exceeded the 2000 to 2022 drought, the recent PRB drought ending in 2022 was the lowest 23-year period in approximately 500 years, acknowledging that uncertainty increases as we move further back in time. When examining paleo and observed AMJJ streamflow records, deficit and surplus periods were evaluated, focusing on the potential “whiplash” between drought and pluvial events. We observed an increase in the frequency of whiplash events, which may be associated with a changing climate.